Evaluation of the effect of aloe vera gel compared with lanolin oil in healing of foot crack disease: A clinical trial study - Maryam Saeidi; Fatemeh Zareie; Vahid Naseri Salahshoor; Rezvan Ghafarzadegan; Fereshteh Javaheri Tehrani (Institue of Medicinal Plants, ACECR, 2019)
BACKGROUND AND OBJECTIVE: Foot Fissure is one of the most common diseases of the foot. This study was conducted to evaluate the effect of aloe vera gel and lanolin oil on the healing process of foot fissure in the Saveh city. METHODS: In this interventional study that performed on 94 patients with foot fissure in both feet, the demographic information questionnaire, dry feet clinical assessment scale and the visual analogue scale (VAS) were used. The subjects in the first intervention group used the aloe vera gel, while the second intervention group used lanolin. The samples of the control group received placebo matched with the original medicine. Finally, the data were analyzed using statistical SPSS software, Ver. 23. FINDINGS: The analysis of datachr('39')s indicated no significant differences between the three groups before the intervention regarding the feet dryness. But, two weeks after the intervention, the mean scores of dry feet in the intervention I group (Aloe Vera) was obtained significantly lower than in the intervention II group (lanolin) (P = 0.027). Also, the scores from visual analogue scale of the foot dryness showed no significant differences in the three groups before the intervention, while after the intervention, the mean visual analog score of the intervention I group was significantly (P = 0.007) lower than in the intervention II group. CONCLUSION: The results of this study show a more favorable effect of aloe vera in comparison with lanolin in healing of dryness and foot cracking.